ANALISIS KEBIJAKAN PEMUNGUTAN RETRIBUSI PELAYANAN PERSAMPAHAN KEBERSIHAN DALAM RANGKA PENINGKATAN PENDAPATAN ASLI DAERAH DI KOTA BANDAR LAMPUNG - Pertiwi Agustina RA; Lintje Anna Marpaung; Herlina Ratna Sumbawa Ningrum (PRANATA HUKUM, 2020)
The policy of the collection of hygiene waste service in order to increase the regional genuine income has been implemented but not maximally. The implementation is done by planning, implementing a means or a work device that facilitates the implementation of the collection of waste services effectively and efficiently and implement the mechanism of retribution and implement a clear evaluation system. The inhibitory factors of the implementation of the collection of waste services/hygiene is still low understanding of the subject of retribution of local legal products concerning the levy of waste services/hygiene and still low awareness of the subject of retribution to the levy which is considered to be incriminated due to feel the obligation of paying tax to Bandar Lampung city government.